2022
DOI: 10.1021/acsami.2c08117
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Electronic Engineering of Vanadium Oxide-Based 3D Lithiophilic Sandwiched-Aerogel Framework for Ultrastable Lithium Metal Batteries

Abstract: Lithium (Li) metal is one of the most promising anode materials for the next-generation batteries, which owns superior specific capacity and energy density. Unfortunately, lithium dendrites that is formed during the charging/discharging process tends to induce capacity degradation and thus short lifespan. In this study, the vanadium oxide (V 2 O 5 ) and nitrogendoped vanadium oxide (N−V 2 O 3 , N−VO 0.9 )-modified threedimensional (3D) reduced graphene oxide ((N)−VO x @rGO) with tunable electronic properties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The technique avoids the usage of polymeric binders and conductive additives and reduces the overall weight of the final device, thereby increasing the gravimetric energy density. Earlier, few attempts have been made to synthesize different VO phases via electrodeposition and these have been employed for supercapacitors and rechargeable battery applications. Ghosh et al reported electrodeposited V 2 O 5 cathodes for an aqueous zinc ion battery in the coin cell configuration; the cell has shown an impressive initial capacity of 510 mAh/g at 0.25 A/g . However, the cell lacks flexibility in design and the traditional coin cell configurations of the fabricated devices cannot support the advanced flexible electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The technique avoids the usage of polymeric binders and conductive additives and reduces the overall weight of the final device, thereby increasing the gravimetric energy density. Earlier, few attempts have been made to synthesize different VO phases via electrodeposition and these have been employed for supercapacitors and rechargeable battery applications. Ghosh et al reported electrodeposited V 2 O 5 cathodes for an aqueous zinc ion battery in the coin cell configuration; the cell has shown an impressive initial capacity of 510 mAh/g at 0.25 A/g . However, the cell lacks flexibility in design and the traditional coin cell configurations of the fabricated devices cannot support the advanced flexible electronic devices.…”
Section: Introductionmentioning
confidence: 99%